Analisis Desain Pembelajaran Culturally Responsive Teaching dalam Konteks Penguatan Literasi Humanistik di Sekolah Dasar - Syafaatul Udmah; Endang Wuryandini; Pipit Mahyasari (Universitas Cokroaminoto Palopo, 2024)
The development of the increasingly advanced century at this time has resulted in humanistic literacy at the elementary school level being eroded, learning about humanistic values, history, and culture in elementary schools is disappearing and resulting in the character values of students becoming more and more deteriorating. The CRT learning model is a solution to this problem that can be done for now. Culturally Responsive Teaching (CRT) is a theoretical approach that aims to help students accept and reinforce their cultural identity, as well as improve learning achievement. Humanistic literacy is the basis of behavior in society and participation in social life that is important to be improved. his research aims to strengthen humanistic literacy by using the Culturally Responsive Teaching (CRT) approach in order to introduce Indonesia's cultural diversity to students, this is expected to help students understand the cultural richness that exists in Indonesia, as well as become individuals who are able to appreciate and respect the cultural diversity around them. The sample of this study is grade IV students of SD Negeri Palebon 01, Semarang City. This type of research uses interpretive qualitative research and interpretive qualitative research is an approach in research that focuses on an in-depth understanding of social phenomena from the perspective of the participants or subjects being studied. The data collection techniques in this study are observation, interviews, journal reflections and documentation. The data analysis technique in this study is copying data from interviews, observations, analyzing data, and drawing conclusions. The results of the study show that the application of the Cultural Responsive Teaching (CRT) approach is very feasible in optimizing humanistic literacy in elementary schools. This learning design emphasizes the importance of understanding and improving students' social foundation values, as well as incorporating their social values and honing learning preparation.